QUANTITATIVE PHYTOCHEMICAL ANALYSIS OF BIOPHYTUM SENSITIVUM (L.) DC. (OXALIDACEAE) - P. DEVI RAJA RAJESWARI,; K. ARUNA,; K. PRABU,; R. CHIDAMBARAM,; S. RAJA SANKAR, (International Journal of Pharma and Bio Sciences, 2014)
The present study investigates the quantitative analysis of the major bioactive constituents of medicinally important plant Biophytum sensitivum (L.) DC. Flavonoids, alkaloids, phenols were reported in the ethanol extract. Percentage of major elements like carbon, nitrogen, phosphorus, potassium, sodium, calcium, magnesium and sulphur were determined. The significance of the plant in traditional medicine is discussed in the study with respect to the role of the plant in ethnomedicine in India.